Marketing as a Christian Vocation: Called to Reconciliation - Hagenbuch, David J. (Christian scholar's review, 2008)
Among business disciplines, David J. Hagenbuch notes that marketing may be the field that is perceived least often as compatible with Christian vocation. However, when one considers that the central purpose of Christian vocation is reconciliation, that reconciliation is linked inextricably to exchange, and that marketing is the science that facilitates mutually beneficial exchange, it is right to suggest that marketing can be practiced as part of a Christian vocation. Because the practice of marketing does not always align with this normative conceptualization of the discipline, this article offers several suggestions for reconciling marketing’s sometimes disparate practical and theoretical components. Mr. Hagenbuch is Assistant Professor of Marketing at Messiah College.